2004
DOI: 10.1097/01.sla.0000146148.01586.72
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Thirty-Two Consecutive Pediatric Liver Transplants Without Hospital Mortality

Abstract: Progress during the past 15 years has enabled us to perform pediatric liver transplantation with near perfect patient survival. Advances in posttransplant care of the recipients, technical refinements, standardization of surgery and monitoring, and adequate choice of the donor organ and transplantation technique enable these results, which mark a turning point at which immediate survival after transplantation will be considered the norm. The long-term treatment of the transplanted patient, with the aim of avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
76
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 33 publications
15
76
1
3
Order By: Relevance
“…Similar to that shown in Broering and associates, 3 we found that the most common cause of liver failure in children was biliary atresia and Wilson disease, suggesting the important role of early diagnosis to diminish the incidence of liver failure. Regarding cause of liver failure, we found no differences between children older or younger than 2 years.…”
Section: Farzad Vafaei Et Al/experimental and Clinical Transplantatiosupporting
confidence: 73%
See 3 more Smart Citations
“…Similar to that shown in Broering and associates, 3 we found that the most common cause of liver failure in children was biliary atresia and Wilson disease, suggesting the important role of early diagnosis to diminish the incidence of liver failure. Regarding cause of liver failure, we found no differences between children older or younger than 2 years.…”
Section: Farzad Vafaei Et Al/experimental and Clinical Transplantatiosupporting
confidence: 73%
“…These components of metabolic syndrome can increase the risk of cardiovascular disease. [1][2][3][4] As shown in a cross-sectional survey on adult liver transplant, 53% of patients had hypertension, 51% had hyperlipidemia, 37% had hyperglycemia, and 32% of patients had increased waist circumference at least 6 months after operation, with metabolic syndrome observed in 44.5%. 1 Some predisposing factors of metabolic syndrome after liver transplant are immunosuppressive drugs, higher age at time of operation, being male, higher body mass index (BMI) before transplant, pretransplant DM, underlying liver disease, and higher BMI in donors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Portal venous stenosis is relatively a rare vascular complication when compared with arterial and biliary complications after liver transplantation, affecting 2-14% of transplant recipients in children [3][4][5][6]. Since the first successful treatment using percutaneous balloon dilatation by Raby et al [7], several methods of portal venoplasty have been reported for the treatment of portal venous stenosis using percutaneous transhepatic [8], transjugular intrahepatic [9], or transileocolic venous [10] approaches.…”
Section: Introductionmentioning
confidence: 99%